Sudden Death in Patients With Severe Aortic Stenosis: Observations From the CURRENT AS Registry. Issue 11 (23 September 0207) - Taniguchi, Tomohiko; Morimoto, Takeshi; Shiomi, Hiroki; Ando, Kenji; Kanamori, Norio; Murata, Koichiro; Kitai, Takeshi; Kawase, Yuichi; Izumi, Chisato; Kato, Takao; Ishii, Katsuhisa; Nagao, Kazuya; et al.
Abstract : Background: The annual incidence of sudden death has been reported to be low (<1%/year) in asymptomatic patients with severe aortic stenosis (AS), and there is a paucity of data on the risk factors of sudden death in patients with severe AS. Methods and Results: We evaluated the incidence and risk factors of sudden death during the median follow‐up period of 1334 days in the Contemporary Outcomes After Surgery and Medical Treatment in Patients With Severe Aortic Stenosis (CURRENT AS) registry enrolling 3815 consecutive patients with severe AS between 2003 and 2011. The mean age was 78 years, and the prevalences of male sex and prior myocardial infarction were 38% and 8%, respectively. Sudden death occurred in 175 patients without aortic valve replacement. The cumulative 5‐year incidences of sudden death, censored at aortic valve replacement, which accounted for the competing risk, were 9.2% in symptomatic patients and 7.2% (1.4%/year) in asymptomatic patients ( P <0.001). Among 82 asymptomatic patients experiencing sudden death, 54 patients (66%) died abruptly without any preceding symptoms, and 35 (65%) of these sudden deaths occurred within 3 months of the last clinical follow‐up visit. Independent risk factors for sudden death were hemodialysis (hazard ratio [HR] 3.63; 95% confidence interval [CI] 2.42‐5.43), prior myocardial infarction (HR 2.11; 95% CI 1.28‐3.50), body mass index <22 (HR 1.51; 95% CI 1.03‐2.21), peak aortic jet velocity ≥5 m/s (HR 1.76; 95% CI 1.12‐2.78), and left ventricular ejection fraction <60% (HR 1.52; 95% CI 1.08‐2.14). Conclusions: The incidence of sudden death in asymptomatic patients with severe AS might be higher than that reported in previous reports. Several baseline clinical and echocardiographic characteristics were associated with increased risk of sudden death. Clinical Trial Registration: URL:www.umin.ac.jp/ctr/index.htm . Unique identifier: UMIN000012140.